KNOWLEDGE OF PATIENTS FROM CAIS MULHER (ANÁPOLIS - GOIÁS) ABOUT ENDOMETRIOSIS (CIPEEX, 2022)
ENDOMETRIOSIS IS THE PRESENCE OF ENDOMETRIAL TISSUE IN AN ECTOPIC LOCATION, WHICH AFFECTS WOMEN OF CHILDBEARING AGE, COMPROMISING THEIR QUALITY OF LIFE AND POSSIBLY CAUSING INFERTILITY. IT IS DIFFICULT TO DIAGNOSE, SO, DESPITE ITS SIGNIFICANT INCIDENCE, IT IS BELIEVED NOT TO BE WIDELY KNOWN BY WOMEN. IN THIS CONTEXT, IN ADDITION TO THE SCARCITY OF SPECIFIC DATA OBSERVED ON THE SUBJECT, THE OBJECTIVE OF THIS STUDY WAS TO REPORT THE KNOWLEDGE OF THE FEMALE POPULATION OF THE UNIT CENTRO DE ATENO INTEGRAL SAÚDE (CAIS) MULHER ANÁPOLIS, GOIS, ABOUT ENDOMETRIOSIS. THE WORK WAS A CROSS-SECTIONAL QUANTITATIVE ANALYTICAL OBSERVATIONAL STUDY, AND THE INFORMATION WAS COLLECTED THROUGH A STRUCTURED QUESTIONNAIRE PREPARED BY THE AUTHORS AND APPLIED TO THE FEMALE PUBLIC OVER 18 YEARS OLD WHO SOUGHT GYNECOLOGICAL MEDICAL ASSISTANCE AT CAIS MULHER, DURING THE PERIOD OF FEBRUARY/2022 TO SEPTEMBER/2022. THE 100 WOMEN WHO PARTICIPATED IN THE STUDY WERE EVALUATED REGARDING SOCIOECONOMIC INFORMATION AND DIVERSE KNOWLEDGE ABOUT ENDOMETRIOSIS, VERIFYING THAT MOST OF THE INTERVIEWED PATIENTS HAD PRECARIOUS KNOWLEDGE ABOUT THE SUBJECT. MOST OF THE WOMEN EVALUATED HAD ALREADY HEARD ABOUT THE DISEASE (80.0%), BUT ONLY 52.0% OF THIS GROUP COULD MENTION SYMPTOMS. IN ADDITION, IT WAS EVIDENCED HOW THE LEVEL OF EDUCATION INFLUENCES KNOWLEDGE, SINCE THE GROUP WITH THE LEAST KNOWLEDGE ABOUT THE DISEASE WAS THE ILLITERATE GROUP, IN WHICH 80% DID NOT EVEN KNOW THE PATHOLOGY. THEREFORE, ENDOMETRIOSIS IS A DISEASE THAT, DESPITE BEING PREVALENT IN BRAZIL, IS LITTLE KNOWN BY THE POPULATION, WHICH REFLECTS A CLEAR LACK OF HEALTH EDUCATION POLICIES ON THE SUBJECT.